Return migration and in situ urbanization of migrant sending areas: Insights from a survey of seven provinces in China. (August 2021) - Zhu, Yu; Wang, Wenfei Winnie; Lin, Liyue; Shen, Jianfa; Ren, Qiang
Abstract: Based on a survey in seven provinces and drawing on previous evidence of in situ urbanization in the coastal areas, this paper examines the implications of return migration for in situ urbanization of migrants' sending areas in China. It shows that returnees can act as catalysts for in situ urbanization by bringing back entrepreneurship, accrued human, financial, social, cultural and technological capital to facilitate rural-urban socioeconomic transformation of their home areas. The results of logistic regressions further confirm that returnees' individual characteristics and migration occupations significantly increase their probability of engaging in non-agricultural occupations post return. However, they seem to have little impact on returnees' likelihood of working in local urban areas. The results suggest that even though return migrants have exhibited somewhat positive impacts on the development of their home areas, their role is rather limited in promoting in situ rural-urban transformation. A weak industrial base at the origin has been identified as a major barrier for rural-urban transformation, which suggests that strategic measures to strengthen industrial capacity in those migrant sending areas should take place in order to fully unleash return migrants' potential in stimulating in situ urbanization of their home areas. Highlights: Returnees can serve as catalysts for in situ urbanization of their home areas. Returnees bring back human, financial, social, and cultural capital as well as entrepreneurship to rural areas. Individual characteristics and migration occupation significantly affect returnees' uptake of non-farm occupations. However, their effects on returnees' likelihood to work in local urban areas are not significant. Weak industrial base is a major barrier to returnees' contribution to in situ urbanization.